Can Government Hospital Survive in The Era of National Health Insurance? - Ida Ayu Diah Tirta Kosala (Universitas Pendidikan Nasional, 2019)
ABSTRACT Based on the Minister of Health Regulation Number 28 of 2014 concerning the National Health Insurance Program Implementation Program which is needed to fulfill the basic needs of every person who has to pay contributions or contributions that are approved by the government. Health is a basic human need to be able to live a decent and productive life, for this reason it is necessary to carry out quality-controlled health care and costs, through the National Health Insurance (JKN) program organized by the Social Security Organizing Agency (BPJS). Hospitals are needed to implement business strategies with display-based resources in order to be able to compete in a tiered, competency-based referral system. This research was conducted at the Tabanan Regency BRSUD with the aim of finding out the business strategy and efforts made by government hospitals in improving excellent service in the JKN era. This study uses qualitative research with a case study approach. Data collection by interview and documentation study. The sampling technique with purposive sampling, Credibility Test (internal validity) using source triangulation techniques. From the results of the study it can be concluded that the applied business strategy is to improve core competencies (core competency) and hospital capabilities, innovating in all forms of service support and efforts to support excellent service are improving quality, efficiency and financial supply chain to achieve sustainable competitive advantage.